The Development of DC-Nano Grid with Wide-Range Wireless Power Transfer for EVs - Pairindra, Worapong; Khomfoi, Surin; Takorabet, Noureddine; Thounthong, Phatiphat (My University, 2022)
This research paper presents a wireless power supply for electronic or electrical devices such as LED taillights or headlight bulbs on the electric vehicle (EVs). The main objectives of using wireless power transfer (WPT) are cost savings and the prevention of fires caused by the insulation burning due to overheating in the conventional cable. According to commercial necessity, the primary goal of the research is to simplify the power converter and transmission coils. Therefore, a high-frequency half-bridge inverter connected with a resonant tank compensator is selected for this task. The power transfer rate is set at 24V, 24W via the high-frequency inverter with 4SV DC input voltage. Apparently, the wireless power at the point load can be controlled at the desired value by using both MATLAB/Simulink and hardware implementations with different ranges of evaluation.
Keywords: DC-Nano Grid; Resonant Converter; Wide-Range Wireless Power Transfer; Wireless Power Transfer